Efficacy and Safety of the Ketogenic Diet for Mitochondrial Disease With Epilepsy: A Prospective, Open-labeled, Controlled Study - Huang, Lijuan; Li, Hua; Zhong, Jianmin; Yang, Liming; Chen, Guohong; Wang, Dong; Zheng, Guo; Han, Hong; Han, Xiong; Long, Yiqin; Wang, Xu; Liang, Jianmin; et al. (Frontiers in Neurology, 2022)
Background The ketogenic diet (KD) is increasingly used to treat drug-resistant epilepsy because of its favorable effect on seizure reduction. Patients with mitochondrial diseases tend to experience seizures. Therefore, this study aimed to test the efficacy of the KD on participants with mitochondrial diseases in a controlled trial. Methods Participants from fourteen clinical centers who were diagnosed with mitochondrial disease were semi-randomized to either the intervention (KD) or control group. The KD group followed a 3-month KD intervention, while the control group received a 1-month normal diet initially and then a 3-month KD intervention. The primary outcome measure was seizure reduction. Biomarker changes, cognitive impairments, and side effects were also recorded, if available. Result A total of 33 participants were assigned to the KD (n = 22) and control groups (n = 11). In the KD group, 31.8% (7/22) of participants achieved ≥50% seizure reduction after 1 month of diet intervention, which increased to 40.9% (9/22) at 3 months. In the control group, only 18.2% (2/11) of the participants had ≥50% seizure reduction during the normal diet period. After the control group was transferred to the KD, 63.6% (7/11) of participants had >50% seizure reduction, and this rate increased to 72.7% (8/11) at 3 months. The KD also showed high efficacy in participants with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) or pathogenic variants in mitochondrial DNA (mtDNA) (90% and 93.3% response rates, respectively). The most frequent side effects reported at the 3-month review were vomiting, cold, hyperlipidemia, and bloating. Conclusion The KD is a safe and effective therapy for seizure control in mitochondrial diseases, especially MELAS and pathogenic variants of mtDNA. KD intervention can be considered in the management of these patients.